Means of Ensuring the Integrity of the Image and Writing in the Performance of Visual Advertising - Gulnoza Tuychizoda Ibrohim kizi; Ahmedova Nazokat (Research Parks Publishing LLC, 2021)
Radical reforms aimed at improving the quality of education in our country have been considered. This article provides information and suggestions on the methods of developed countries, in the specificity of the text and images in the creation of advertising.